Nowcasting and forecasting aquaponics by Google Trends in European countries - Dos Santos, Maria José Palma Lampreia (2018)
Aquaponics, an innovation in agricultural systems of production and food supply which combines aquaculture fish production with hydroponic production of vegetables, represents a valuable option to overcome the food needs of a constantly increasing world population, it can do so by improving production and supply with less inputs and in a sustainable way. Despite recent developments in this scientific area, there are still not enough commercial firms at a European level that allow for a consistent view of how this activity is evolving in society, as well as, to understand the impact of Aquaponics Hub in promoting the development of this activity in Europe - aquaponics is still at an early age and, despite innovative, it needs time to grow and evolve. Thus, we used Google Trends data and a quantitative methodology, multivariate analysis and econometric models, in order to both nowcast and forecast insights about the importance, the role and the new trends in aquaponics. The results show an interesting trend of increasing popularity in aquaponics search terms as a proxi of aquaponics development in Europe, mainly in all the European countries belonging to the Aquaponics Hub. However, we conclude that there is still a long way to go for aquaponics before it becomes a commercial activity at economic level. Hence, European and public decision-makers are urged to be more concerned about legislation and the allocation of funds for research and for the commercial investment of companies and for their promotion and development in aquaponics.